IMOBILISASI ASAM SALISILAT PADA Mg/Al HYDROTALCITE DAN APLIKASINYA UNTUK ADSORPSI-REDUKSI [AuCl4]Ë - , EKA ROVITA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The application of Mg/Al hydrotalcite-Salicylic Acid (HT-AS) for the adsorption-reduction of [AuCl4]- in aqueous medium has been investigated. Mg/Al hydrotalcite was synthesized by direct coprecipitation method of Mg(NO3)2 and Al(NO3)3 at pH 10.11, with the molar ratio of Mg(II) to Al(III) 2:1 respectively. The synthesized Mg/Al hydrotalcite as well as its immobilization product with salicylic acid (HT-AS) before and after being used to adsorptionreduction [AuCl4]- were characterized by X-ray Diffraction and FT-IR Spectroscopy. The effect of pH adsorption-reduction [AuCl4]-, kinetic and isoterm adsorption, and effect of addition isopropanol as OH radical scavenger were also studied. The gold metal formed was confirmed by difractogram XRD. Immobilization of salicylic acid was reached at pH 5. The analytical result using FTIR and XRD showed that salicylic acid has been immobilized on surface of Mg/Al hydrotalcite with adsorption capacity which was determined according Langmuir isoterm model was 47.62 mg/g. Adsorption-reduction [AuCl4]Ë by HTAS was optimum at pH 3 and followed pseudo-second order kinetic model and Langmuir isotherm model with rate constant (k) and adsorption capacity were 1.1325 x 10-4 g/mg minute and 166.67 mg/g respectively. The characterization results of HT-AS using XRD instrument after adsorption-reduction process of [AuCl4]- showed Au(III) was successfully reduced to Au(0) which was indicated by the appearance of characteristic peaks for Au(0) at 2Î¸ = 37.98